Evaluation of Thrombocyte Functions and General Features of Patients With Myeloproliferative Diseases - Kurtoğlu, Erdal; Hidayetoğlu, Taha; Tunç, Ahmet (Fırat University, 2003)
Aim: Myeloproliferative diseases (MPH) are clonal diseases that are characterized by the proliferation of myeloid precursors. Bleeding and thromboembolism are the major complications. Defects in thrombocyte functions can lead to such complications. Materials and method: We evaluated the findings of physicial examination, laboratory features, complications, and thrombocyte functions of fourty patients (15 polycytemia vera-PV, 13 essential thrombocytemia-ET and 11 chronic myeloid leukemia-CML), 21 female, 19 male, whose median age was 55 (range:23-78) retrospectively. Results: Age of PV patients was significantly higher than that of ET and CML patients. Values of hemoglobin and hematocrit were significantly higher in PV where as thrombocyte count was significantly higher in ET. While leukocyte count was high in all three types of MPD, it was significantly higher in CML than two other diseases (>12x109/L). Rate of leukocytosis was 39% in PV and 25% in ET. While thrombocyte count was higher in all ET patients (>400x109/L), rate of thrombocytosis was 65% for PV and 36% for ET. Splenomegaly was found in 11 (100%) CML patients, 7(46%) PV patients, and 4(31%) ET patients. Thrombocyte aggregation defects was detected in 8 (73%) CML patients, 4 (27%) PV patients, and 6 (55%) ET patients. There was no significant relation between thrombocyte count and aggregation defects. We could not detect any complications other than erithromelalgia in 2 ET patients, and gastrointestinal bleeding in one PV patient. Conclusion: Aggregation defects depending on ADP and epinephrine are the mostly seen ones in MPD. Aggregation defects are independent from the thrombocyte count. In addition it helps us to take protective measures againts any hemostatic defect.

Amaç: Myeloproliferatif hastalıklar (MPH), myeloid seri hücrelerinin kontrolsüz üremesi ile karakterize klonal hastalıklardır. Kanama ve tromboemboli en sık karşılaşılan komplikasyonlardır. Trombosit fonksiyonlarındaki bozukluklar bu tür komplikasyonlara zemin hazırlayabilmektedir. Gereç ve Yöntem: Kliniğimize başvuran ve MPH tanısı konulan 21 kadın, 19 erkek olan 40 hastanın ortanca yaşı 55 (aralık:23-78) (15 polisitemia vera-PV, 13 esansiyel trombositemi-ET ve 11 kronik myeloid lösemi-KML) olguyu laboratuvar, fizik muayene, trombosit fonksiyonları ve komplikasyonlar açısından geriye dönük olarak inceledik. Bulgular: PV'nın görülme yaşı, ET ve KML'den anlamlı olarak yüksek idi. Hemoglobin ve hematokrit değerleri PV'de, trombosit sayısı ise ET'de anlamlı olarak yüksek idi. Lökosit sayıları her üç MPH'ta da yüksek bulunurken, KML'deki lökosit sayıları diğer iki hastalıktan anlamlı olarak yüksek idi (>12x109/L). Lökosit sayısı, PV olgularının %39'unda, ET olgularının ise %25'inde yüksek bulundu. Tüm ET olgularında trombosit sayısı yüksek (>400x109/L) bulunur iken; PV olgularının %65'inde ve KML olgularının %36'sında trombositoz saptandı. Splenomegali, 11 (%100) KML, 7 (%46) PV ve 4 (%31) ET olgusunda saptandı. KML olgularının 8'inde (%73), PV olgularının 4'ünde (%27) ve ET olgularının 6'sında (%55) trombosit agregasyon bozukluğu bulundu. Trombosit sayısı ile trombosit agregasyon bozukluğu arasında herhangi anlamlı bir ilişki saptanmadı. Yalnızca 2 ET olgusunda saptanan eritromelalji dışında herhangi bir komplikasyon saptayamadık. Sonuç: ADP ve epinefrine bağlı olarak gelişen trombosit agregasyon bozukluğu MPH'da en sık karşılaşılan agregasyon defektleridir. Agregasyon defekti, trombosit sayısından bağımsız olarak gerçekleşebilmektedir. Ayrıca, hasta bazında olgunun hemoztaz bozukluğunun saptanıp gerekli önlemlerin alınmasını sağlayabilir.
Myeloproliferatif Hastalıklı Olgularımızın Trombosit Fonksiyonlarının ve Genel Özelliklerinin Değerlendirilmesi